Navigating WASH challenges in rural areas: Peer effects and infrastructure - Zhanna Kapsalyamova; Kamalbek Karymshakov; Dina Azhgaliyeva (Asian Development Bank Institute (ADBI), 2024)
Despite the well-documented benefits of improved sanitation and washing facilities, a considerable number of people, even in middle-income countries, still lack access to modern sanitation and home-based bathing facilities. This paper leverages household budget survey data from two Central Asian countries to investigate the barriers to improved adoption of sanitation and washing facilities. The study finds that in Kazakhstan, households with higher incomes generally have better sanitation facilities. Households led by married individuals have better facilities in both Kazakhstan and the Kyrgyz Republic. The average adoption rate in a sub-province also contributes to an increased household-level sanitation and washing facilities uptake. This suggests that peer influences represent an important mechanism underlying household behavior. The role of infrastructure is significant. Access to piped water increases the probability of adoption of modern sanitation and washing facilities in both countries. Primary barriers to the adoption of better sanitation and washing facilities by rural households include the lack of necessary infrastructure (piped water and centralized sewerage).
Keywords: I12; O12; O18; J16; 330; WASH; sanitation; Central Asia; rural households; structural estimation